Esoteric Buddhism in mediaeval maritime Asia: networks of masters, texts, icons - Acri, Andrea (Nalanda-Sriwijaya series, 2016)
This volume advocates a trans-regional, and maritime-focused, approach to studying the genesis, development and circulation of Esoteric (or Tantric) Buddhism across Maritime Asia from the seventh to the thirteenth centuries CE. The book lays emphasis on the mobile networks of human agents ('Masters'), textual sources ('Texts') and images ('Icons') through which Esoteric Buddhist traditions spread. Capitalising on recent research and making use of both disciplinary and area-focused perspectives, this book highlights the role played by Esoteric Buddhist maritime networks in shaping intra-Asian connectivity. In doing so, it reveals the limits of a historiography that is premised on land-based transmission of Buddhism from a South Asian 'homeland', and advances an alternative historical narrative that overturns the popular perception regarding Southeast Asia as a 'periphery' that passively received overseas influences. Thus, a strong point is made for the appreciation of the region as both a crossroads and rightful terminus of Buddhist cults, and for the re-evaluation of the creative and transformative force of Southeast Asian agents in the transmission of Esoteric Buddhism across mediaeval Asia.